Entrepreneurship Village Program in Sukoharjo, Sleman Through Development of Agricultural Products - Rokhana Dwi Bekti; Marsailes Nipu; Simona Iskandaria Nurak (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Tanjungsari Hamlet is one of the hamlets located in Sukoharjo Village, Ngaglik District, Sleman Regency, Special Region of Yogyakarta. Tanjungsari have the potential for agricultural products that can be developed into superior products. Two agricultural products are chili and gadung. Chili agricultural products are usually directly sold to nearby markets without being processed first, which can harm the community when chili prices fall. Meanwhile, for gadung tubers, there are already business actors who process them into gadung chips but still use traditional tools so that the products produced are of less quality and the marketing is less extensive. Another obstacle in optimizing chili and gadung results is human resources that have not been supported, namely not having the ability to process products and market them. Therefore, the program provided is the Entrepreneurial Village Program for the development of chili and gadung agricultural products into ready-to-eat chili sauce and Gadung Chips "TJS". The method used is training and mentoring. The target of this program is two groups’ people, which each group consisting of 10 farmers who cultivate chili and gadung tubers. To overcome the problems that occur, an entrepreneurial village program has been carried out from July-December 2023. Programs that have been implemented include training programs for processing chili peppers into ready-to-eat chili sauce, training on processing taste variations, providing packaging, providing processing tools, marketing research, promotional media and developing sales systems, and institutions. The product name is called "Sambal TJS" and "Keripik Gadung TJS". After all the programs, the conclusion are the people in Tanjungsari Village have products that are ready to be marketed and also gaining knowledge about marketing TJS products and how to build a business network and marketing.